PROGRAM BIMBINGAN PRIBADI SOSIAL UNTUK MENINGKATKAN KETERAMPILAN SOSIAL PESERTA DIDIK KELAS VIII (STUDI DESKRIPTIF DI SMP NEGERI 12 BANDUNG TAHUN AJARAN 2019-2020) - Dewi Indah Dahlia, - (2019)
Dewi Indah Dahlia 1506956 (2019), Personal Social Guidance Program to Increase the Students' Social Skill (Descriptive Study for the 8th Grade Students in State Junior High School 12 Bandung Academic year 2019/2020), Psychology of Guidance and Counselling, Faculty of Education Science, Indonesian University of Education. This study is motivated by the importance of the 8th grade students' social skill to easily adjust themselves to their new classmates and to fulfil the developmental task in adolescence. The aim of this study is to know the 8th grade students' social skill profile in State Junior High School 12 Bandung Academic year 2019/2020. This study uses quantitative approach through descriptive method. The sample of the study are the 8th grade students of State Junior High School 12 Bandung Academic year 2019/2020. This study presents: (1) the social skill profile of the 8th grade students are categorized into medium level; (2) the formulation of social personal guidance program based on the result of study about the obtained social skill of the 8th grade students. The recommendation is given to school and guidance and counselling teacher to implement the formulated personal social guidance program. Keywords: social skill, students, personal social guidance program